Peran Filsafat Islam dalam Membangun Pendidikan di SD Muhammadiyah PK Bayat - Khotimah, Anisa Nur; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
The role of philosophy in Islamic education is united by a common goal, namely the search for truth. However, the difference is that philosophy is more about reason while Islamic education means efforts to advance the character (inner strength), mind (intellect), and body of students who must be in harmony with the natural and social environment. The purpose of this study is to determine the role of Islamic philosophy in building education at Muhammadiyah Elementary School PK Bayat. The research method is a literature review which contains several ideas and proportions related to the study supported by data and information obtained from library sources. Some of the findings produced include education as a process of preparing a generation to live life and fulfill its life goals effectively and efficiently. The problems of Islamic education are approached with the framework of the hadharah triangle. From this conceptual development, the aim is to change into a visionary, integrative-interconnective, non-dichotomous Islamic education that can answer contemporary issues. These principles are woven into a concept of progressive and civilized Islamic education. Philosophical research is intended to examine the thoughts of figures and their educational concepts.